Culture and the periphery: Nomadic wanderings in the Argentine sociology of culture - Alabarces, Pablo Alejandro (2012)
This work presents both a history and an overview of current production in the Argentine sociology of culture. Based on the so-called double periphery - the peripheral location of Argentine sociology in the western social sciences, but also of cultural research within local sociology - the author seeks to analyze the emergence of this subdiscipline. It owes to both the concern for mass culture and its relationship with populism at the end of the 1960s. At that time, these studies were being done by researchers with training in literary criticism, researchers who approached cultural phenomena as a political concern, in a way similar to what occurred when British cultural studies were born. At the end of Argentina's last dictatorship (1976-1983), the reappearance and growth of a sociology of culture expanded into Nomadic terrains and into varied themes and institutions: this was due to a proliferation of studies in social communication and new university departments, but it can also be attributed to the influence of Brazilian anthropology. Another factor is the delayed creation of graduate programs and their clearly multidisciplinary nature. Today the field is testing its potential while undergoing both quantitative and qualitative growth. However, it is essential to re-examine the field's sociological aspects as it moves along this path.